THE USE OF FOREIGN EXPERIENCE IN ACHIEVING A HIGH QUALITY INDICATOR IN THE FIELD OF PRESCHOOL EDUCATION - Karimova Shoira Baxtiyarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article discusses the application of advanced foreign experience in achieving the effectiveness of education in the system of preschool education, comparative study and analysis of the system of education, the practical application of educational technologies.